Operational Risk Control Strategy in Sharia Cooperatives - Nur Kholis; Vivin Maharani Ekowati (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
This research aims to identify risk management strategies in the LKS Al Yasini sharia cooperative. LKS Al Yasini is a sharia-based financial institution located in Pasuruan, East Java. This study is important to carry out because operational risks still occur frequently and will always occur, although in different and new forms. Therefore, sharia cooperatives need to improve their operational risk management to maintain their existence and increase member trust. The research method used in this research is descriptive with a field research approach. The results of this research indicate that implementing security system improvements and enhancements is very important for sharia cooperatives to control potential risks that may arise. The implications of this research provide an important contribution in increasing understanding of operational risk management in the context of Islamic financial institutions and can serve as a guide for improvements and enhancements in the future.